Lévy walk dynamics explain gamma burst patterns in primate cerebral cortex - Yuxi Liu (Nature Portfolio, 2021)
Liu et al used a combination of empirical observation and modeling to investigate high-frequency (gamma band) local field potential activity in visual motion-processing cortical area MT of marmosets. They found that gamma bursts are organised as localised patterns that propagate across the cortical surface with Lévy walk dynamics and hypothesized that such dynamics could help the cortex to efficiently process variable inputs.